Analysis of the Relationship Between the Development of Performance Criteria and Job Performance of Employees With Respect to the Mediating Role of Employee Participation - Fallahnejad , Ali; Nazari, Reza; Fard , Mehdi Moradzadeh (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2023)
The main purpose of this study is to investigate and analyze Positive and significant impact of defining employee performance criteria with the objectives: evaluation, empowerment and career development on the job performance of Keshavarzi Bank of Iran employees with regard to the mediating role of employee participation. The present study was based on the purpose of applied research and in terms of the method was a descriptive-survey study. A questionnaire was used to collect research data. The statistical population of the present study consisted of senior and middle managers of the Keshavarzi Bank of Iran who had at least 5 years of work experience. The number of these people in the initial studies was estimated at 483 and finally, using Cochran's formula, 215 people were selected as the sample size. After collecting data through a questionnaire, data analysis was performed using structural equation modeling. The results showed that the development of performance criteria with the objectives of evaluating, empowering, and developing the career path of employees has a positive and significant effect on the job performance of employees of the Keshavarzi Bank of Iran. Supplementary results also showed that employee participation in the relationship between the three objectives of developing performance criteria and job performance of employees has an effective mediating role, so this effect in the relationship between performance criteria to develop a career path and job performance of employees with the path coefficient of 0.684 is very obvious. Accordingly, it can be said that since employee participation is the basis for the development of service organizations such as banks, by implementing measures related to employee participation and benefiting from employees' opinions in formulating performance criteria, preparations for achieving an effective performance management system. And thus accelerated the movement of the Keshavarzi Bank of Iran on the path of development.